Credit Risk in Regional Development Banks: The Roles of Operational Inefficiency, Profitability, and Independent Commissioners - Iqbal Alfahruli; L. Lutfi (Manunggal Halim Jaya, 2026)
This study examines the effects of operational inefficiency, profitability, and independent commissioners on credit risk in Indonesian Regional Development Banks (RDBs). Regional Development Banks (RDBs), locally known as Bank Pembangunan Daerah, are provincially owned financial institutions that play a vital role in promoting regional economic development. Credit risk remains a major concern for RDBs because of their strategic intermediation function and their vulnerability to non-performing loans (NPLs). Using panel data from 23 conventional RDBs over the 2018–2024 period, this study analyzes 161 bank-year observations through panel data regression, with the Random Effect Model identified as the most appropriate estimation technique. Credit risk is measured by the non-performing loan (NPL) ratio, operational inefficiency by the operating expense-to-operating income (OEOI) ratio, profitability by return on equity (ROE), and board independence by the number of independent commissioners. The findings reveal that operational inefficiency has a positive and significant effect on credit risk, indicating that lower cost efficiency increases the deterioration of loan quality. In contrast, profitability has a negative and significant effect on credit risk, suggesting that more profitable banks are better able to maintain asset quality and absorb potential losses. Independent commissioners also have a negative and significant effect on credit risk, demonstrating the importance of board independence in strengthening oversight and mitigating risk. However, independent commissioners do not moderate the relationships between operational inefficiency and credit risk or between profitability and credit risk. This study contributes to the banking and corporate governance literature by providing empirical evidence from Indonesian RDBs, an underexplored segment of the banking industry in emerging markets. The findings suggest that, rather than functioning as a moderating mechanism, independent commissioners serve as an important direct governance mechanism for mitigating credit risk. From a practical perspective, RDBs should improve operational efficiency, maintain sustainable profitability, and strengthen board independence to enhance credit risk management and support long-term financial stability.